2013
DOI: 10.1007/s00425-013-1923-z
|View full text |Cite
|
Sign up to set email alerts
|

Nematode feeding sites: unique organs in plant roots

Abstract: Although generally unnoticed, nearly all crop plants have one or more species of nematodes that feed on their roots, frequently causing tremendous yield losses. The group of sedentary nematodes, which are among the most damaging plant-parasitic nematodes, cause the formation of special organs called nematode feeding sites (NFS) in the root tissue. In this review we discuss key metabolic and cellular changes correlated with NFS development, and similarities and discrepancies between different types of NFS are h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
130
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(136 citation statements)
references
References 85 publications
2
130
1
3
Order By: Relevance
“…Microarray transcript abundance studies of laser-capture microdissected syncytium samples have indicated that Rhg1-mediated disease resistance is accompanied by a cellular stress profile that includes oxidative, cold, osmotic, and unfolded protein stresses (43). Additionally, the high metabolic demands and large-scale membrane reorganizations necessary to form the syncytium (16)(17)(18) may amplify cellular sensitivity to noncooperative α-SNAPs, even in cases where there may be a less significant shift in the ratio of resistance-type Rhg1 α-SNAPs to wild-type α-SNAPs. A study of virulent SCN populations that had recently evolved to reproduce on soybeans carrying high-copy Rhg1 haplotypes demonstrated allelic imbalance of a SNARE-like effector protein in the nematode (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray transcript abundance studies of laser-capture microdissected syncytium samples have indicated that Rhg1-mediated disease resistance is accompanied by a cellular stress profile that includes oxidative, cold, osmotic, and unfolded protein stresses (43). Additionally, the high metabolic demands and large-scale membrane reorganizations necessary to form the syncytium (16)(17)(18) may amplify cellular sensitivity to noncooperative α-SNAPs, even in cases where there may be a less significant shift in the ratio of resistance-type Rhg1 α-SNAPs to wild-type α-SNAPs. A study of virulent SCN populations that had recently evolved to reproduce on soybeans carrying high-copy Rhg1 haplotypes demonstrated allelic imbalance of a SNARE-like effector protein in the nematode (44).…”
Section: Discussionmentioning
confidence: 99%
“…Syncytium formation is a complex process involving plant cell-wall dissolution, endoreduplication, cell-cell fusion, and membrane reorganization, with the eventual incorporation of over 100 host root cells into one large multinucleate cell (15,16,18). Because egg-filled SCN cysts can persist in fields for many years and nematicides are often costly and environmentally damaging, the two core SCN control strategies are crop rotation to reduce inoculum load and use of SCN-resistant soybean varieties.…”
Section: Significancementioning
confidence: 99%
“…The role of ethylene in plant-nematode interactions is complex (reviewed in Kyndt et al, 2013). Although ethylene biosynthesis genes responded slightly faster to nematode infection in TOG5681 in comparison with 'Nipponbare', a complex pattern of repression and activation was observed in both the incompatible and compatible interactions.…”
Section: Role Of Hormonal Pathways Is Complexmentioning
confidence: 99%
“…These obligate parasites initiate a long period of biotic interactions with their host plants where formation of an operative feeding structure, the syncytium, is vital for nematode survival and development. The nematode provokes differentially terminated cells in the vascular root tissues to redifferentiate into a syncytium cell type, a dynamic process that involves changes in the expression of thousands of genes simultaneously (Hewezi and Baum, 2013;Kyndt et al, 2013;Hewezi, 2015). Though the mechanisms controlling gene expression changes in the syncytium remain ill defined, recent studies indicate that epigenetic mechanisms including noncoding small RNAs and DNA methylation may play fundamental roles (Hewezi and Baum, 2015).…”
mentioning
confidence: 99%